Effects of Oral L-Carnitine on Liver Functions after Transarterial Chemoembolization in Intermediate-Stage HCC Patients. (19th November 2015) - Hassan, Abeer; Tsuda, Yasuhiro; Asai, Akira; Yokohama, Keisuke; Nakamura, Ken; Sujishi, Tetsuya; Ohama, Hideko; Tsuchimoto, Yusuke; Fukunishi, Shinya; Abdelaal, Usama M.; Arafa, Usama A.; Hassan, Ali T.; et al.
Abstract : Transarterial chemoembolization (TACE) is usually followed by hepatic dysfunction. We evaluated the effects of L-carnitine on post-TACE impaired liver functions. Methods . 53 cirrhotic hepatocellular carcinoma patients at Osaka Medical College were enrolled in this study and assigned into either L-carnitine group receiving 600 mg oral L-carnitine daily or control group. Liver functions were evaluated at pre-TACE and 1, 4, and 12 weeks after TACE. Results . The L-carnitine group maintained Child-Pugh (CP) score at 1 week after TACE and exhibited significant improvement at 4 weeks after TACE (P < 0.01 ). Conversely, the control group reported a significant CP score deterioration at 1 week (P < 0.05 ) and 12 weeks after TACE (P < 0.05 ). L-carnitine suppressed serum albumin deterioration at 1 week after TACE. There were significant differences between L-carnitine and control groups regarding mean serum albumin changes from baseline to 1 week (P < 0.05 ) and 4 weeks after TACE (P < 0.05 ). L-carnitine caused prothrombin time improvement from baseline to 1, 4 (P < 0.05 ), and 12 weeks after TACE. Total bilirubin mean changes from baseline to 1 week after TACE exhibited significant differences between L-carnitine and control groups (P < 0.05 ). The hepatoprotective effects of L-carnitine were enhanced by branched chain amino acids combination. Conclusion . L-carnitine maintained and improved liver functions after TACE.